Lexical and Structural Ambiguity Found in Articles in The Jakarta Post Daily Newspaper - Puspitasari, Julie; Sutjiati Beratha, Ni Luh (Humanis; Vol 23 No 1 (2019)DO - 10.24843/JH.2019.v23.i01.p04, 2019)
This study aims at finding out lexical and structural ambiguity which occurs in the articles and explaining the causal factors in each ambiguity. The data in this study were taken from nineteen articles in The Jakarta Post daily newspaper from edition November 14 to November 25, 2017. Recording method and note taking technique were applied in this study for collecting the data. Meanwhile, the data were analyzed using qualitative method. Ulmann’s theories that involved kinds of ambiguity and the causal factors of ambiguity, by using Macmillan Dictionary to find the definition of each word in lexical ambiguity and labeled and bracketed sentences/phrases proposed by Yule were used to analyze the data. The result of the analysis shows that there were 20 ambiguous words, phrases or/and sentences found in nineteen articles in The Jakarta Post. There were 8 cases of lexical ambiguities and 12 cases of structural ambiguities. The result of this study shows the causal factors of each ambiguity as well, there were 8 lexical ambiguities caused by polysemy and 12 structural ambiguities caused by equivocal phrasing.